(3eUfa GHf CHj TjHIs - (3CHh HcQ YHO Gddg Hf eMeO Hf CHj TjHI GdYHSj, GHf CHj TjHI,J (B235 (3g` s
(3ChdgG (B:s
(3jHJOF HaUd ai GdMfhW cja jUfY HgG hCjf JLYd ef cJGH GdLfGFR s
(3BNQgG (B:s
(3jfJgi HaUd cja JYad GdHOf ef cJGH GdML s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B117s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1711s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs